323 Association Between Biofilm Production and Antibiotic Resistance in Acinetobacter Clinical Isolates. (11th January 2018) - Ghaith, Doaa
Abstract: Objectives: We aimed to determine the association between biofilm production and antibiotic resistance in Acinetobacter clinical isolates. Methods: A total of 100 clinical isolates of Acinetobacter were collected from clinical settings in Cairo, Egypt. The antibiogram of Acinetobacter isolates showed high resistance percentage to the most tested antibiotics by Vitek2 automated system. The ability of these isolates to produce biofilm was determined by different methods, with the tissue culture plate method (microtiter plat method) regarded as the gold standard method as it is the most accurate; it has determined 24 isolates as high producers, 34 isolates as moderate producers, and 42 isolates as weak producers of biofilm. Results: Testing of antibacterial activities of eight essential oils against the 12 selected biofilm producing Acinetobacter isolates revealed that only four essential oils—cinnamon, clove, thyme, and eucalyptus—exhibited promising antibacterial activity against the test isolates, so we tested these selected oils against biofilm production. Out of the four oils, only cinnamon has shown promising antibiofilm activity against the test isolates. GC/MS analysis of the most active essential oil revealed that cinnamaldehyde in cinnamon was the main component in the oil. Testing of antibiofilm activities of the major component (ie, cinnamaldehyde) of the most active oil (ie, cinnamon oil) against the selected biofilm producing Acinetobacter isolates demonstrated a lower antibiofilm activity of cinnamaldehyde against the tested isolates, compared to cinnamon oil. Conclusion: Our data suggest that essential oils can represent promising natural components suitable for use as antibacterial and antibiofilm agents with a particular interest for the pharmaceutical industry as they are inexpensive compounds.